ANALISIS KEPUASAN PEGAWAI TERHADAP LAYANAN UNIT SISTEM INFORMASI MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL DI PT KERETA API INDONESIA (PERSERO) - Yuda Yuliana; Rangga Sanjaya; Mayya Nurbayanti Shobary (Jurnal Informatika, 2016)
AbstractSatisfaction in work is an individual thing. Each individual will have a level of satisfaction varies according to the system of values prevailing in him. This study was conducted to determine the level of employee satisfaction with the services in the information systems unit PT Kereta Api Indonesia (Persero) in order to get results that can make service information systems unit to be better again. Based on the analysis of Multiple Linear Regression method Technology Acceptance Model , obtained the result that the employees satisfied with the usability factor ( Perceived Usefulness ) the variable Perceived Usefulness and Perceived Ease of Use influencing variable Attitude Toward Using With his existing results of scientific research , the expected improvement in the quality of services provided to the employee information systems unit. Keywords: Employee Satisfaction, Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using.